THE CAPACITY OF THIRD COUNTRIES TO NEGOTIATE BILATERAL AGREEMENTS WITH THE UK UNDER WITHDRAWAL ARRANGEMENTS (EU and comparative law issues and challenges series (ECLIC), 2019)
Having in mind that this is the first time that a Member State decided to withdraw from the EU pursuant to Article 50 TEU there are many aspects of this process that attract the attention of scholars studying EU related issues. Regardless of the outcome of the ongoing political debate and the course of action that will be taken eventually, after the CJEU decision in Wightman, we deem the need to further explore the extent of Article 50 and its implications on a number of stakeholders self- evident. In this paper we will deal with the capacity of non-EU countries to negotiate and conclude bilateral agreements with the UK i.e. a country withdrawing from the EU. The analysis is based on the proposed framework under the Draft Agreement on the withdrawal of the United Kingdom of Great Britain and Northern Ireland from the EU and the Euratom and the possible interpretation and understanding of terms “the principle of sincere cooperation” and “the Union’s interest” in this context, the principles of international law including the provisions of the Vienna Convention on the Law of Treaties and the general principles of Union law. The primary focus is on the legal uncertainty the lack of a more thorough approach creates to non- EU countries, especially to third countries aspiring to join the EU. Considering that they do not participate in the withdrawal negotiations, it is a challenge for them to take part in prospect bilateral negotiations with the UK, while, at the same time, making sure they stay on their EU path. We argue in favor of the deal, as a universally accepted approach in case of future withdrawals, not only for the purpose of establishing a reference for any future application of Article 50, but also for providing legal certainty to those parties that are not prima facie affected by the withdrawal, but that do have to act in accordance with all deals made without the right to be heard.